2009
DOI: 10.1016/j.jtcvs.2008.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of intratumoral vessel invasion in completely resected pathologic stage I non–small cell lung cancer

Abstract: The current study indicated that intratumoral vessel invasion and pleural invasion are independent prognostic factors. Intratumoral vessel invasion status can complement the size-dependent TNM staging system in pathologic stage I non-small cell lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 30 publications
1
44
0
2
Order By: Relevance
“…Although the clinic-pathologic staging system has been the standard for determining NSCLC prognosis [2], this classification scheme is probably an imprecise predictor of the prognosis of an individual patient. Five-year survivals in resected stage IA and IB disease were 67-89% and 57-75%, respectively [3,4]. One of the reasons for this variation is that stage I NSCLC includes populations with a different grade of malignancy [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the clinic-pathologic staging system has been the standard for determining NSCLC prognosis [2], this classification scheme is probably an imprecise predictor of the prognosis of an individual patient. Five-year survivals in resected stage IA and IB disease were 67-89% and 57-75%, respectively [3,4]. One of the reasons for this variation is that stage I NSCLC includes populations with a different grade of malignancy [4].…”
Section: Introductionmentioning
confidence: 99%
“…Five-year survivals in resected stage IA and IB disease were 67-89% and 57-75%, respectively [3,4]. One of the reasons for this variation is that stage I NSCLC includes populations with a different grade of malignancy [4]. This observation underlines how important it is to identify novel pathological parameters in addition to disease stage and, most of all, new biological markers, in order to add further prognostic information, select high-risk patients for aggressive adjuvant treatments [5].…”
Section: Introductionmentioning
confidence: 99%
“…Intratumoral vessel invasion (IVI) of lymphatic vessels (IVI-L) or blood vessels (IVI-V) is an important pathological factor for lung carcinoma, both because it predicts metastasis and it has been shown to be an independent determinant of a poor prognosis in non-small cell lung carcinoma, especially in the early stages [5][6][7]. In addition, adjuvant chemotherapy can be beneficial for patients with stage IA lung carcinoma with IVI [8].…”
Section: Introductionmentioning
confidence: 99%
“…Vascular invasion is associated with unfavorable prognosis in NSCLC (Bodendorf et al 2009;Gabor et al 2004;Kessler et al 1996;Miyoshi et al 2009;Poncelet et al 2008;Rigau et al 2002). We previously reported that vascular invasion could be classified as intratumoral or extratumoral, according to its location (Maeda et al 2010).…”
Section: Discussionmentioning
confidence: 99%